Strukturna analiza asistenc pri vrhunskih košarkarskih ekipah - Zadnik, Uroš (Šport (Ljubljana), 2024)
Reciprocal peer teaching refers to the independent learning of students in pairs in which they swap tutee and tutor roles. This modern teaching approach allows for greater impact on the psychomotor and conceptual learning of students at different educational levels and in different sports disciplines. The aim of our study was to compare the success of students in practical and theoretical examinations in athletics after experiencing peer teaching or direct instruction. We included 140 students from the Faculty of Sport in the study. Knowledge was measured after 45 hours of instruction using nine motor tests and a written theoretical examination. We calculated the homogeneity of variances and the normal distribution of the dependent variables and then compared the differences in the post-test using the Independent t-test or its non-parametric alternative. We found that the students in the experimental group performed better than those in the control group in both the practical and theoretical tests. However, the differences were not statistically significant. Despite this result, we believe that the introduction of modern teaching approaches into the educational programmes of physical educators makes sense. Indeed, current literature shows that the training of students – prospective PE teachers – has a positive impact on the knowledge and skills of their students.
Keywords: asistenca; assist; basketball; European Championship; evropsko prvenstvo; košarka; sport; šport; technique; tehnika